2018
DOI: 10.2478/hukin-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Strength Training Programs in Handball Players and its Influence on Power During the Competitive Period

Abstract: A high level of muscle power is necessary for the effective use of technique during handball competitions. The presented research concentrated on comparing the effectiveness of two training modes directed towards the development of muscle power – plyometric and traditional strength training. Furthermore, we evaluated whether resistance training performed twice a week was sufficient to guarantee an increase in muscle power of handball players. We also investigated whether strength training designed according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
2
23
0
2
Order By: Relevance
“…However, this hypothesis was rejected since no significant differences in reliability were observed between the Aver3, Aver4, and MAX procedures. There is not consensus in the scientific literature on which procedure to use for selecting the final throwing velocity outcome with some researchers using the average velocity of several trials [2,[28][29][30], others researchers using the maximum value [3,11,31,32], and others researchers who do not even report the procedure followed to select the final test outcome [2,10,14,22,[33][34][35]. Of note is that this is the first study to compare the reliability of throwing velocity between different procedures commonly used in the scientific literature to select the final test outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this hypothesis was rejected since no significant differences in reliability were observed between the Aver3, Aver4, and MAX procedures. There is not consensus in the scientific literature on which procedure to use for selecting the final throwing velocity outcome with some researchers using the average velocity of several trials [2,[28][29][30], others researchers using the maximum value [3,11,31,32], and others researchers who do not even report the procedure followed to select the final test outcome [2,10,14,22,[33][34][35]. Of note is that this is the first study to compare the reliability of throwing velocity between different procedures commonly used in the scientific literature to select the final test outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity in the procedures used to select the final test outcome also compromises the comparison of throwing velocity between different studies. For example, some studies reported the average velocity value of the recorded trials [2,[28][29][30], others the maximum value [3,11,31,32], and others did not specify the procedure used to select the final test outcome [2,10,14,22,[33][34][35]. In relation to this, the average countermovement jump (CMJ) height of several trials has been recommended over the maximum value because it seems to be more sensitive for monitoring the neuromuscular status [36], but not similar analyses have been performed for throwing velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the training programs, it has been found that programs targeted at the inspiratory muscles not only improve these muscles in particular, but also contribute to enhancing aerobic performance ( Hartz et al, 2018 ) and postural stability exercises implementing the biofeedback method on stabilo and dynamometric platforms are practical and justifiable in junior goalkeepers ( Wilczyński, 2018 ). Pre-season conditioning programs that include working on hamstring and quadriceps muscles are needed to reduce the risk of injury ( Spieszny and Zubik, 2018 ). Furthermore, proper planning of training in adolescents that allows them to improve their levels of strength and maximum power is necessary ( Górski et al, 2018 ).…”
mentioning
confidence: 99%
“…Maintaining and even improving the levels of the muscle strength developed in the preparatory period of the season is the main task during the playing season. However, applying strength training during the playing season is also a demanding task since all the other motor abilities need to be maintained at high levels avoiding tiring out the players, which can lead to the state of their being overtrained (Spieszny & Zubik, 2018;Silvestre et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The basis of those activities are muscle strength, speed and endurance, which are crucial for the successful performance of all the technical and tactical tasks set for the players (Ohnjec et al, 2008;Granados, Izquierdo, Ibañez, Bonnabau, & Gorostiaga, 2007). The role and importance of explosive strength in handball have been the subject matter of a lot of research (Spieszny & Zubik, 2018;Mir & Bari, 2017;Marques, 2010;Gorostiaga, Izquierdo, Iturralde, Ruesta, & Ibanez, 1999;Hoff & Almasbakk, 1995). The explosive strength of the lower extremities is responsible for the realization of various types of jumps, running speed and acyclic handball-specific movements (Carvalho, Mourão, & Abade, 2014;Ĉavala et al, 2008).…”
Section: Introductionmentioning
confidence: 99%